2012
DOI: 10.1159/000341704
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling in Onset and Progression of Hepatocellular Carcinoma

Abstract: Transforming growth factor (TGF)-β is a central regulator in chronic liver disease, contributing to all stages of disease progression from initial liver injury through inflammation and fibrosis to cirrhosis and hepatocellular carcinoma. Liver damage-induced levels of active TGF-β enhance hepatocyte destruction and mediate hepatic stellate cell and fibroblast activation resulting in a wound-healing response, including myofibroblast generation and extracellular matrix deposition. Further evidence points to a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 105 publications
2
55
1
Order By: Relevance
“…TGF-β is a well-established fibrotic cytokine that plays a vital role in the pathophysiology of MF as well as other fibrotic diseases (15,17,(19)(20)(21)(37)(38)(39)(40)(41)(42). Elevated levels of the TGF-β1 isoform were detected in plasma and bone marrow serum in MF mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β is a well-established fibrotic cytokine that plays a vital role in the pathophysiology of MF as well as other fibrotic diseases (15,17,(19)(20)(21)(37)(38)(39)(40)(41)(42). Elevated levels of the TGF-β1 isoform were detected in plasma and bone marrow serum in MF mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Among the abnormally expressed cytokines in MF, TGF-β1 has received attention due to its critical role in inducing fibrosis not only in bone marrow (15)(16)(17)(18), but other organs (19)(20)(21). TGF-β1 may be produced by abnormal megakaryocytes or monocytes, and this in turn may remodel the MSCs that promote the changes illustrated by MF (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Several components of the TGF-b signaling pathway are lost or inactivated in various epithelial neoplasms [14]. However, only a fraction of liver tumors exhibit inactivating mutations [15,16], so other mechanisms perturbing hepatocytic TGF-b signaling appear critical in human hepatocarcinogenesis [17]. On the other hand, TGF-b as well as proinflammatory cytokines such as tumor necrosis factor (TNF)-a and interleukin-6 can synergistically promote fibrogenesis by stimulating ECM deposition in activated mesenchymal cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…The TGF-β subfamily of cytokines includes a series of multifunctional proteins [25] and participates in many biological processes such as inflammation, wound healing, the generation and accumulation of extracellular matrix, and so on [26] . The relationship between TGF-β and fibrosis is reflected in many diseases [27] . Studies showed that trabecular meshwork cells synthesized and secreted TGF-β, and TGF-β influenced the synthesis of the extracellular matrix in primary open-angle glaucoma by regulating connective tissue growth factor [28] .…”
Section: The Relationship Between Mirna and The Extracellular Matrix mentioning
confidence: 99%